Pumped-Storage Scheduling Using Glowworm Swarm Algorithm - Chen, Po-Hung (Proceedings of Engineering and Technology Innovation, 2017)
This paper presents new solution methods and results based on a glowworm swarm algorithm for solving the 24-hour pumped-storage generation scheduling problem. Complete solution algorithms and encoding/decoding techniques are proposed in the paper. The optimal schedules of both pumped-storage and thermal units are concurrently obtained within the evolutionary process of evaluation functions. Significantly, no hydro-thermal iteration is needed. The proposed approach is applied with success to an actual utility system, which consists of four pumped-storage units and 34 thermal units. The results indicate the attractive properties of the glowworm swarm algorithm in practical application, namely, a highly optimal solution cost and more robust convergence behaviour.